Costs and benefits of economic integration in Asia - Barro, Robert J.; Lee, Jong-Wha. (New York ; Oxford : Oxford University Press, 2010)
After financial disaster, the world's economy is changing drastically, and Asia will play a pivotal role in how these changes occur. This is an essential reference on the controversy and consensus on economic integration, and how it will influence individual Asian countries, the region as a whole, and the world, for decades to come.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Asia -- Economic integration; Asia -- Economic policy -- 21st century